Genomics data of L. borgpetersenii strain HP364 and L. weilii strain SC295 isolated from rodents captured from human leptospirosis outbreak areas in Selangor, Malaysia - Neela, Vasantha Kumari; Philip, Noraini; Raja, Pappitha; Sekawi, Zamberi (American Society for Microbiology, 2023)
We report complete genome sequences of two Leptospira isolates, Leptospira borgpetersenii strain HP364 and Leptospira weilii strain SC295. The genome sizes of L. borgpetersenii strain HP364 and L. weilii strain SC295 were 3,874,738 bp and 4,063,712 bp, respectively. Both genomes have been deposited in NCBI GenBank.